Sustainable development of vernacular architecture: a systematic literature review - Zong, Jia; Wan Mohamed, Wan Srihani; Zaky Jaafar, Mohamad Fakri; Ujang, Norsidah (Taylor and Francis Group, 2024)
The sustainable evolution of vernacular architecture effectively addresses climate change and environmental challenges, yet comprehensive reviews are scarce. Therefore, this study aimed to explore the history and progression of vernacular architecture and address the requisite knowledge and methodologies for its sustainable development via a systematic literature review. A meticulous screening process of relevant articles was performed in two research databases (Scopus and Web of Science) using the keywords “Cave-dwelling,” “Kiln building,” “Historical architecture,” and “Vernacular architecture” that represents vernacular architecture and “Sustainable” and “Green building” for sustainability. A total of 36 articles published between 2019 and 2023 were then selected for the quantitative and qualitative analyses using the ATLAS.ti 23 software. The result revealed five major themes: 1) Cultural characteristics of vernacular architecture; 2) Structure of vernacular architecture; 3) Vernacular architecture environment; 4) Renewal and utilisation of vernacular architecture; and 5) Assessment criteria in vernacular architecture. In summary, the current research on vernacular architecture remains primarily focused on architectural studies, with minimal consideration from the user’s viewpoint. Thus, it is essential to enhance the comfort and functionality of vernacular architecture, preserve its local culture, and meet the users’ demands.